Development and evaluation of an anthropometric module for digital human modelling systems. (6th September 2019) - Brolin, Erik; Högberg, Dan; Hanson, Lars; Örtengren, Roland
This paper presents the development of a software module and a graphical user interface which aims to support the definition of anthropometry of manikins in a digital human modelling (DHM) tool. The module is developed from user interviews and literature studies, as well as mathematical methods for anthropometric diversity consideration. The module has functionality to create both single manikins and manikin families, where it is possible to combine or analyse different population datasets simultaneously. The developed module and its interface have been evaluated via focus group interviews and usability tests by DHM tool users. Results from the studies show that the developed module and its interface has relevant functionality, fits well into industrial work processes, and is easy to use. The study also identifies possibilities to further increase usability.